Le qṣar, type d'implantation humaine au Sahara : architecture du Sud Algérien - Chekhab-Abudaya, Mounia (Cambridge monographs in African archaeology, 2016)
This volume reveals common architectural features that can be used to identify a common type of qsar in the Sahara region.